2021
DOI: 10.1021/acsomega.1c02150
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Different Growth Mechanisms of Sodium Chlorate under the Same Experimental Conditions

Abstract: Dependence of growth rates of {100} sodium chlorate crystal faces on solution supersaturation in the range of 0.44–1.32% was analyzed. It has been shown that the growth rate dispersion does not have a consequence only in the growth parameter differences predicted by specific crystal growth theory but that individual crystal faces may grow with different mechanisms under the same experimental conditions. The majority of the observed {100} sodium chlorate crystal faces grew in accordance with the power law … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…It was recently shown that the {100} faces of sodium chlorate crystals can grow by different mechanisms in the supersaturation range of 0.44–1.32%. 17 The functions describing the spiral growth were found to be practically linear for supersaturations higher than 0.89% ( Figure 2 ). 17 Negative values of the growth rate have no physical meaning, but in theories of spiral growth, the intercept of the linear function with the abscissa has the meaning of critical supersaturation, σ c .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It was recently shown that the {100} faces of sodium chlorate crystals can grow by different mechanisms in the supersaturation range of 0.44–1.32%. 17 The functions describing the spiral growth were found to be practically linear for supersaturations higher than 0.89% ( Figure 2 ). 17 Negative values of the growth rate have no physical meaning, but in theories of spiral growth, the intercept of the linear function with the abscissa has the meaning of critical supersaturation, σ c .…”
Section: Discussionmentioning
confidence: 94%
“…The functions describing the spiral growth were found to be practically linear for supersaturations higher than 0.89% (Figure ). Negative values of the growth rate have no physical meaning, but in theories of spiral growth, the intercept of the linear function with the abscissa has the meaning of critical supersaturation, σ c . Its estimated value for the experiments presented is 0.19%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A feedback system was applied to regulate the growth rate of an anchored crystal which served as an indicator for controlling growth conditions of suspended target crystals in the same solution. However, the work acknowledged that controlling of the indicator crystal does not necessarily ensure the quality of the target crystals because different growth mechanisms can coexist within the same solution 31 , and did not study the correlation between linear growth rate and crystal quality. Moreover, the longest growth time was only 6 h, resulting in target crystal sizes remaining <1 mm.…”
Section: Frc With Feedback Loopmentioning
confidence: 99%